Job Discrimination and Ethics in the Workplace - Furxhi, Gentisa; Prof. as. dr. Sonela Stillo; Msc. Enslemvera Zake (Furxhi) (European Journal of Multidisciplinary Studies, 2016)
Every society wants to have an ethical community. Although, that every citizen wants to be treated as equal, studies show that discrimination and gender inequality in employment relationships are present in every society, at any time. Discrimination is: treating a person or particular group of people differently, especially in a worse way from the way in which you treat other people, because of their skin color, sex, sexuality, etc . Job discrimination is when institutional decisions, policies, or procedures are at least partially based on illegitimate forms of discrimination that benefit or harm certain groups of people. Developed societies have a lower rate of job discrimination than developing societies have. Although, it is unclear why in these societies with economic civilization and culture development, job discrimination still exists, when the right of employment is sanctioned and guaranteed by Labor Code and by specific laws. The most common forms of job discriminations are discriminations based on gender, race, ethnic origin, religion, age. New forms are based on disability, sexual orientation, genetics and lifestyle. Not all discrimination is intentional or conscious. Sometimes people favor some groups of people over others as a matter of personal preference, or unconsciously accept stereotypes. Whatever, job discrimination is intentional or it is conscious, it is always immoral. Job discriminations violates utilitarian, rights and justice principles of ethics. Our study is focused to see how much job discriminations is widespread in Albanian society. We will analyze forms of discriminations to have a clear view which are the most common job discriminations types in Albania. Also, we will figure out if employees who have been discriminated in the workplace, have reported this unethical behavior to their supervisor or at the relevant state bodies. At the end, we will see if there has been any punishment to those who use discrimination to the employees.